"Three Subunit" Classification of Lesser-Form Cleft Lip and Muscle Analysis and Reconstruction of These Subunits Based on the Microanatomic Structures of Muscles in the Normal Upper Lip. Issue 6 (September 2019) - Sun, Min; Wang, Yong Q.; Li, Hai D.; Wu, Di; Yin, Ning B.; Song, Tao
Abstract : Background: The main phenotypic features of lesser-form cleft lip include nasal, philtrum, and vermilion deformities. The manifestations of lesser-form cleft lip vary greatly, and it is difficult to rebuild these subunits during the operation. Methods: "Three subunits" classification of lesser-form cleft lip was identified as nasal deformity (N), philtrum deformity (P), or vermilion deformity (V); and slight deformity (0) or obvious deformity (1). A total of 200 patients with lesser-form cleft lip were classified into one of the following 8 types: N1P1V1, N1P1V0, N0P1V1, N1P0V1, N0P0V1, N1P0V0, N0P1V0, or N0P0V0. Then the authors discussed the deformities of the lesser-form cleft lip and the reconstruction of the muscles in these subunits based on the microanatomic structure of the nasolabial muscle. Results: This retrospective review included 200 patients with a lesser-form cleft lip, who were seen at our center from 2015 to 2017. There were 149 (74.5%) N1P1V1, 11 (5.5%) N1P1V0, 13 (6.5%) N0P1V1, 4 (2.0%) N1P0V1, 8 (4.0%) N0P0V1, 10 (5.0%) N1P0V0, 1 (0.5%) N0P1V0, and 4 (2%) N0P0V0 clefts. The various deformities of nasal floor, philtrum ridge, and vermilion may suggest that the muscle bundles in these subunits are abnormal and the operation should be performed to simulate the running directions and tension lines of these local muscles. Conclusions: The microanatomic structure and the tension lines of the nasolabial muscles can provide new perspectives for better understanding and repairing the lesser-form cleft lip in subunits.